Dynamic Changes in the Levels of Amyloid-β42 Species in the Brain and Periphery of APP/PS1 Mice and Their Significance for Alzheimer’s Disease - Zhang, Liding; Yang, Changwen; Li, Yanqing; Niu, Shiqi; Liang, Xiaohan; Zhang, Zhihong; Luo, Qingming; Luo, Haiming (Frontiers in Molecular Neuroscience, 2021)
Although amyloid-β42 (Aβ42) has been used as one of the core biomarkers for Alzheimer’s disease (AD) diagnosis, the dynamic changes of its different forms in the brain, blood, and even intestines and its correlation with the progression of AD disease remain obscure. Herein, we screened Aβ42-specific preferred antibody pairs 1F12/1F12 and 1F12/2C6 to accurately detect Aβ42 types using sandwich ELISA, including total Aβ42, Aβ42 oligomers (Aβ42Os), and Aβ42 monomers (Aβ42Ms). The levels of Aβ42 species in the brain, blood, and intestines of different aged APP/PS1 mice were quantified to study their correlation with AD progression. Total Aβ42 levels in the blood were not correlated with AD progression, but Aβ42Ms level in the blood of 9-month-old APP/PS1 mice was significantly reduced, and Aβ42Os level in the brain was significantly elevated compared to 3-month-old APP/PS1, demonstrating that the levels of Aβ42Ms and Aβ42Os in the blood and brain were correlated with AD progression. Interestingly, in 9-month-old APP/PS1 mice, the level of Aβ42 in the intestine was higher than that in 3-month-old APP/PS1 mice, indicating that the increased level of Aβ42 in the gastrointestinal organs may also be related to the progression of AD. Meanwhile, changes in the gut microbiota composition of APP/PS1 mice with age were also observed. Therefore, the increase in Aβ derived from intestinal tissues and changes in microbiome composition can be used as a potential early diagnosis tool for AD, and further used as an indicator of drug intervention to reduce brain amyloid.